2016
DOI: 10.3892/br.2016.702
|View full text |Cite
|
Sign up to set email alerts
|

Screening for minimal hepatic encephalopathy in patients with cirrhosis by cirrhosis-related symptoms and a history of overt hepatic encephalopathy

Abstract: Abstract. The diagnosis of minimal hepatic encephalopathy (MHE) is more difficult in comparison to the diagnosis of overt hepatic encephalopathy (OHE), as patients with MHE do not exhibit overt neurological deficits and must be diagnosed using specialized equipment. However, identifying MHE is critical for patients with cirrhosis, and a simple screening test is required. The present study aimed to evaluate the associations between MHE, clinical characteristics and questionnaire items regarding sleep disturbanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 27 publications
2
14
1
Order By: Relevance
“…A poor sleeper had 10 or more points on the ESS and 6 or more points on the PSQI. We have previously shown that minimal hepatic encephalopathy is correlated with 9 or more points on the CSS . Psychological distress is defined as 13 points or more on the K‐6.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A poor sleeper had 10 or more points on the ESS and 6 or more points on the PSQI. We have previously shown that minimal hepatic encephalopathy is correlated with 9 or more points on the CSS . Psychological distress is defined as 13 points or more on the K‐6.…”
Section: Resultsmentioning
confidence: 99%
“…An “impact factor” for each item was calculated, which was defined as the product of the frequency of the item and the mean importance that the patients attributed to the item. The impact factor for each item ranged from 0 to 3, and the CSS was calculated as the sum of the impact factors . The ESS was used to evaluate daytime hypersomnolence; ESS scores range from 0 to 24, and a score of ≥10 indicates significant daytime hypersomnolence.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mild defects of MHE cognitive function can sometimes be detected through specific methods such as mental assessment scales or neuropsychiatric testing. Currently, a worldwide consensus on the diagnostic criterion for MHE is absent, and the diagnosis of MHE is difficult . It is common to use more than two sensitive neuropsychological tests.…”
Section: Discussionmentioning
confidence: 99%
“…The cirrhosis-related symptom scores (CSS) questionnaire, which we developed, was used to evaluate cirrhosis symptoms [9]. The Epworth Sleepiness Scale (ESS) was used to evaluate daytime hypersomnolence [10].…”
Section: Questionnairesmentioning
confidence: 99%